PSX-B-2 Effect of feedlot days on intake and performance of Nellore heifers. (8th October 2021) - Ferreira, Igor M; Cidrini, Iorrano A; Souza, William; Abreu, Mateus I; Prados, Laura F; Lage, Josiane F; Siqueira, Gustavo; Resende, Flávio
Abstract: The objective was to evaluate the effect of feedlot days (FD) on intake (DMI) and performance of Nellore heifers. Fifty-one Nellore heifers [325±19.3 kg of body weight (BW); 16±1 months], blocked by initial BW and stratified by carcass ultrasound, were divided into three treatments: 45, 75 or 105 FD; and placed in 18 pens [17 heifers/treatment; 6 pens/treatment (5 pens with 3 heifers and 1 pen with 2 heifers)]. The animals were fed ad libitum allowing 3% of refusals. The diet consisted of corn silage, ground corn, soybean meal, protected fat and minerals. The adaptation diet [16% CP and 79% TDN; roughage:concentrate (R:C) = 44:56] was offered from day 1 to 15 and the finishing diet from day 16 to 105 (14.5 % CP and 86% TDN; R:C = 25:75). At the end of each FD, heifers were weighted to obtain the shrunk final BW and slaughtered in the same slaughterhouse. The final BW and hot carcass weight (HCW) were greater (linear effect; P ≤ 0.01), respectively, for heifers on 105FD (442 and 244 kg) compared to 75FD (411 and 228 kg) and 45FD (374 and 206 kg). The DMI, backfat thickness and longissimus area increased over FD (linear effect; P ≤ 0.01; 45FD = 7.10 kg/d, 5.05 mm and 64.3 cm 2 ; 75FD = 7.68 kg/d, 5.69 mm and 68.5 cm 2 and 105FD=7.79 kg/d, 7.04 mm and 73.3 cm 2 ). The FD did not affect carcass gain (P = 0.38) and feed efficiency based on carcass gain (P = 0.84). However, total carcass gain increased over FD (linear effect; P ≤ 0.01; 29, 51.4 and 75.9 kg, respectively to treatments 45, 75 and 105 FD). In conclusion, the feedlot days increase the BW, backfat thickness and longissimus area. However, the feed efficiency based on carcass gain does not reduce when the heifers are submitted for a long time on feedlot.